2010
DOI: 10.1515/jpem.2010.185
|View full text |Cite
|
Sign up to set email alerts
|

Graves' Disease in a Down's Syndrome Patient

Abstract: Thyroid dysfunction in patients with Down's syndrome is well known. Although the majority of children with Down's syndrome appear to have normal thyroid function, however, hypothyroidism is commonly seen. The presence of hyperthyroidism is rare. The etiology is believed to be autoimmune. We report a patient with Down syndrome and Graves' disease who responded well to antithyroid drugs. The rarity of this association, especially in a child younger than eight years of age, has prompted us to report this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…From the limited data available from India it appears that the patients of DS with hyperthyroidism from India are younger and do not show any gender predilection. [ 8 9 10 ] This observation is consistent with that of the largest published Italian and Spanish series. Considering the 1/449 to 2/700 incidence of DS among the live births the total burden of DS with thyroid dysfunction including hyperthyroidism is likely to be higher in India.…”
Section: Discussion and Review Of Literaturesupporting
confidence: 89%
See 1 more Smart Citation
“…From the limited data available from India it appears that the patients of DS with hyperthyroidism from India are younger and do not show any gender predilection. [ 8 9 10 ] This observation is consistent with that of the largest published Italian and Spanish series. Considering the 1/449 to 2/700 incidence of DS among the live births the total burden of DS with thyroid dysfunction including hyperthyroidism is likely to be higher in India.…”
Section: Discussion and Review Of Literaturesupporting
confidence: 89%
“…Published literature from India is scanty and documents only four cases including this case report of hyperthyroidism in DS. [ 8 9 10 ] In a published Indian study of 300 children with DS from 2004 to 2014, 82 patients were found to have abnormal thyroid hormone profiles with 76 patients having subclinical hypothyroidism and the rest overt hypothyroidism. [ 11 ] No patient in this review study was found to have hyperthyroidism.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…The prevalence of GD has been reported at a higher rate in children with DS than in the general population ( 25 ), but overall, it is rare ( 4 ). Therefore, it is not remarkable that almost all data on GD in children with DS has been published as case series with case numbers ranging from 1 to 4 cases ( 8 , 9 , 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical course and outcome of GD in children with DS have been investigated in a limited number of case series with case numbers ranging from one to four cases ( 8 , 9 , 10 , 11 ). Generally, GD in DS children is symptomatic, easy to diagnose, and often associated with other autoimmune diseases ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In DS, both HT and GD occur at a younger age than in the general population (between late childhood and early adolescence), without gender preference and frequently in association with other autoimmune disorders [75,77,96,97].…”
Section: Down Syndromementioning
confidence: 99%